2012
DOI: 10.2209/tdcpublication.53.75
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Sotos Syndrome Treated with Distraction Osteogenesis in Maxilla and Mandible

Abstract: Sotos syndrome is inherited in an autosomal-dominant manner and is characterized by increased birth weight, excessive growth, advanced bone age, and distinctive facial features, including dolichocephaly, hypertelorism, and a prominent mandible. We treated a jaw deformity due to Sotos syndrome consisting of malocclusion due to a narrow maxillary dental arch and mandibular retrusion from hypoplasia of the rami. The patient was a 17-year-old man. Malocclusion due to a narrow maxillary dental arch and mandibular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
1
0
3
Order By: Relevance
“…Sotos sendromu tipik yüz görünümü: alın çıkıklığı, hiperteleroizm veya telekantus, kemerli burun, düşük düzeyde palpebral fissur, yüksek kubbe damak (Şekil 1), aşırı büyüme (baş çevresi/boy >2.5 SD) ve öğrenme güçlüğü ile karakterizedir. Ayrıca davranışsal problemler, konjenital kardiyak anomaliler, yenidoğan sarılığı, renal anomaliler, skolyoz ve nöbetler de eşlik edebilir (8). Pes planus, sindaktili, büyük el ve ayak ve hemihipertrofi gibi extremite bulguları da görülebilir (9-10).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sotos sendromu tipik yüz görünümü: alın çıkıklığı, hiperteleroizm veya telekantus, kemerli burun, düşük düzeyde palpebral fissur, yüksek kubbe damak (Şekil 1), aşırı büyüme (baş çevresi/boy >2.5 SD) ve öğrenme güçlüğü ile karakterizedir. Ayrıca davranışsal problemler, konjenital kardiyak anomaliler, yenidoğan sarılığı, renal anomaliler, skolyoz ve nöbetler de eşlik edebilir (8). Pes planus, sindaktili, büyük el ve ayak ve hemihipertrofi gibi extremite bulguları da görülebilir (9-10).…”
Section: Discussionunclassified
“…Bu güne kadar yaklaşık 400 olgu bildirilmiştir. Hastalığın prevalansı bilinmemekle birlikte yaklaşık 1/10000 ile 1/50000 arasında olduğu tahmin edilmektedir (8). Literatürde otozomal dominant kalıtımın etkili olduğunu düşündüren, birbirini takip eden altı jenerasyonda benzer bulgular saptanan bir aile bildirilmiş olmasına karşın olguların çoğu sporadiktir (11).…”
Section: Discussionunclassified
“…10 14 Sotos sendromunda NSD1 geninin mutasyonuna bağlı olarak maksiller dişlerin labiale açılanmalarında artış, mandibula gelişiminde gerilik, posterior cross-bite görülmektedir. 15 Literatüre bakıldığında distraksiyon osteogenezi ile tedavi edilen maxiller ve mandibular hipoplaziye bağlı bir retrüzyon vakası 16 ve süt dişlerinde yaygın hipoplazi bulgulanan bir vaka 17 ile premolar hipodontisinin gözlendiği bir vaka serisi bildirilmiştir. 18 Bu hastalar maloklüzyon, dental sağlık ve eşlik edebilecek oral komplikasyonlar açısından takip edilmelidirler.…”
Section: Sendromununclassified
“…Maxillary distraction osteogenesis has shown successful results in the treating the patients suffering from Crouzon syndrome [40,41,42], Sotos Syndrome [43], traumatic or oncologic surgical maxillofacial resections [44,45], and severe maxillary hypoplasia in cleft lip and palate [46,47]. Studies have shown distraction osteogenesis to be a better option than orthognathic surgery for the treatment of patients requiring moderate to large advancements with significant structural deficiencies of the maxilla [48].…”
Section: Combined Mandible and Lefort I Distractionmentioning
confidence: 99%